Methodical bases of working out of analytical model of enterprise financial condition - Akanayeva, Т.А. (Ye.A.Buketov Karaganda State University Publ., 2014)
Article is devoted to a problem of improvement of the financial analysis at the domestic enterprises, in particular to modeling of a financial condition. The dependence equations between separate indicators of accounting financial statements by means of use of economic-mathematical tools on the example of one of the largest industrial enterprises of the North Kazakhstan area — JSC «Munaymash» are considered. The author makes recommendations about forecasting of a financial condition of the enterprise by means of its modeling by means of which probably in due time to make changes to the program of development of the enterprise and effectively to operate resources for achievement of the maximum financial result.
Кəсіпорын қаржылық жағдайының аналитикалық моделін əзірлеудің əдістемелік негіздері
Методические основы разработки аналитической модели финансового состояния предприятия
Keywords: financial analysis; financial stability of the enterprise; modeling of financial condition; business activity; linear models; solvency; liquidity; creditability; Profitability